Negative electrode material, preparation method thereof and lithium ion battery
By forming a carbon material cladding layer on the surface of the silicon-based negative electrode material, the problem of poor volume expansion and rate performance of the silicon-based negative electrode material in lithium-ion batteries is solved, and higher cycling performance and stability are achieved.
Patent Information
- Application Number
- CN202311277415.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The existing silicon-based anode materials have problems such as large volume expansion and poor rate performance in lithium-ion batteries, which affect their wide application.
A silicon-based material including silicon oxide and lithium silicate is used and a carbon material coating is formed on its surface. The structure and performance of the coating are optimized through vapor deposition technology and the use of solid or liquid phase coating agents.
It effectively reduces the volume expansion of the negative electrode material, improves its rate performance and cycling performance, enhances the stable interface construction of the electrolyte, and reduces the loss of active silicon and lithium.
Smart Images

Figure CN119725415A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials, and in particular to negative electrode materials and preparation methods thereof, and lithium ion batteries. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, high cycle life, low environmental pollution and no memory effect, so they are widely used in electric vehicles and consumer electronic products. The negative electrode material is an important component of lithium-ion batteries, which directly affects key indicators such as battery energy density, cycle life and safety performance. With the continuous improvement of the mileage requirements of new energy vehicles in practical applications, power battery-related materials are also developing in the direction of providing higher energy density. The graphite negative electrode of traditional lithium-ion batteries can no longer meet the existing demand, and high energy density negative electrode materials have become a new hot spot pursued by companies.
[0003] Silicon-based negative electrode materials are one of the most critical materials for high-energy-density lithium-ion batteries. However, existing silicon-based negative electrode materials have problems such as large volume expansion and poor rate performance, which affect the widespread application of silicon-based negative electrode materials in lithium-ion batteries. At present, single carbon material coating is a more conventional coating option. Conductive carbon can improve the conductivity of the material, but the existing carbon material coating layer still has many defects.
[0004] Therefore, developing a negative electrode material with excellent cycle performance and low volume expansion effect and a preparation method thereof are still technical challenges in the field. Summary of the invention
[0005] The purpose of the present application is to provide a negative electrode material and a preparation method thereof, and a lithium-ion battery, which can reduce the volume expansion of the negative electrode material and improve the rate performance and cycle performance of the negative electrode material.
[0006] In a first aspect, an embodiment of the present application provides a negative electrode material, the negative electrode material comprising a silicon-based material and a coating layer located on at least a portion of the surface of the silicon-based material, the silicon-based material comprising silicon oxide and lithium silicate, and the material of the coating layer comprising a carbon material;
[0007] 20 mg of the negative electrode material is dissolved in 10 ml of deionized water to form a slurry, and the slurry is subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50 mV to -40 mV is I1, the maximum intensity of the second characteristic peak in the Zeta potential range of -65 mV to -50 mV is I2, and the maximum intensity of the third characteristic peak in the Zeta potential range of -35 mV to -25 mV is I3, and the relationship between I1, I2, and I3 satisfies: 0≤I2 / I1≤2.0, 0≤I3 / I1≤1.0.
[0008] In some embodiments, the carbon material includes at least one of graphite, amorphous carbon, diamond-like carbon, carbon fiber, and carbide.
[0009] In some embodiments, the carbon material includes silicon carbide.
[0010] In some embodiments, the material of the coating layer further includes at least one of nitride, metal oxide, phosphate and silicate.
[0011] In some embodiments, the material of the coating layer further includes nitride, and the nitride includes at least one of silicon nitride, pyrrole, and pyridine.
[0012] In some embodiments, the material of the coating layer further comprises a metal oxide, and the metal oxide comprises at least one of titanium oxide, aluminum oxide, magnesium oxide, lithium oxide, zirconium oxide, cobalt oxide and vanadium oxide.
[0013] In some embodiments, the material of the coating layer also includes phosphate, and the phosphate includes at least one of lithium phosphate, aluminum phosphate, lithium aluminum phosphate, lithium titanium aluminum phosphate, magnesium phosphate, lithium magnesium phosphate, calcium phosphate, lithium calcium phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and triammonium phosphate.
[0014] In some embodiments, the material of the coating layer further includes silicate, and the silicate includes at least one of lithium silicate, magnesium silicate, aluminum silicate, magnesium aluminum silicate, lithium magnesium silicate, calcium silicate, magnesium calcium silicate, lithium calcium silicate and lithium aluminum silicate.
[0015] In some embodiments, the coating layer has a thickness of 20 nm to 700 nm.
[0016] In some embodiments, the silicon-based material has a median particle size of 2.0 μm to 10.0 μm.
[0017] In some embodiments, the mass content of lithium in the silicon-based material is 10 3 ppm~105 ppm.
[0018] In some embodiments, the general formula of the lithium silicate is Li2O-nSiO2, wherein 0<n≤4.
[0019] In some embodiments, the lithium silicate is located on at least a portion of the surface of the silicon oxide.
[0020] In some embodiments, the lithium silicate is located on at least a portion of the surface of the silicon oxide, and the lithium silicate is dispersed on the surface of the silicon oxide.
[0021] In some embodiments, the median particle size of the negative electrode material is 2 μm to 12 μm.
[0022] In some embodiments, the specific surface area of the negative electrode material is 0.5 m 2 / g~8.0m 2 / g.
[0023] In some embodiments, the tap density of the negative electrode material is 0.5 g / cm 3 ~3.0g / cm 3 .
[0024] In some embodiments, the mass content of water in the negative electrode material is 0.01% to 0.5%.
[0025] In some embodiments, based on 100% of the mass of the negative electrode material, the mass of the carbon material accounts for 0.5 wt % to 10 wt %.
[0026] In some embodiments, based on 100% of the mass of the negative electrode material, the mass content of lithium in the negative electrode material is 2% to 15%.
[0027] In some embodiments, the pH of the negative electrode material is 10.0-12.3.
[0028] In a second aspect, an embodiment of the present application provides a method for preparing a negative electrode material, comprising the following steps:
[0029] Providing a pre-lithium silicon-based material, wherein the silicon-based material comprises silicon oxide and lithium silicate;
[0030] A gas-phase carbon source is used to perform gas phase deposition on a pre-lithiation silicon-based material, and a solid-phase coating agent and / or a liquid-phase coating agent are simultaneously added for gas phase deposition to obtain a negative electrode material, wherein the negative electrode material comprises a silicon-based material and a coating layer located on at least a portion of the surface of the silicon-based material, the coating layer comprises a carbon material formed by deposition of the solid-phase coating agent and / or the liquid-phase coating agent and a carbon material formed by deposition of the gas-phase carbon source, and the solid-phase coating agent and / or the liquid-phase coating agent contain a benzene ring structure.
[0031] In some embodiments, the step of providing a pre-lithiation silicon-based material comprises: performing a pre-physical and chemical treatment on a mixture containing silicon oxide and a lithium source to obtain the pre-lithiation silicon-based material.
[0032] In some embodiments, the silicon oxide is silicon monoxide.
[0033] In some embodiments, the lithium source includes at least one of lithium hydride, alkyl lithium, metallic lithium, lithium hydroxide, lithium amide, lithium borohydride, and lithium silicon alloy.
[0034] In some embodiments, the mass ratio of the silicon oxide to the lithium source is (85-99):(1-15).
[0035] In some embodiments, the pre-treatment time is 0.5h to 24.0h.
[0036] In some embodiments, the temperature of the pre-treatment is 300°C to 1000°C.
[0037] In some embodiments, the pre-chemical treatment is performed under an inert gas atmosphere, and the inert gas atmosphere includes at least one of helium, neon, argon, krypton and xenon.
[0038] In some embodiments, before subjecting the mixture containing silicon oxide and lithium source to pre-physical and chemical treatment, the method further comprises: subjecting the silicon oxide and lithium source to mixing and then subjecting the silicon oxide to shaping treatment to obtain the mixture containing silicon oxide.
[0039] In some embodiments, before subjecting the mixture containing silicon oxide and lithium source to pre-physical and chemical treatment, the method further comprises: mixing the silicon oxide and lithium source and then subjecting them to shaping treatment to obtain silicon oxide, wherein the shaping treatment comprises at least one of crushing, ball milling, grinding and gas crushing.
[0040] In some embodiments, before vapor-depositing the silicon-based material using a vapor-phase carbon source, the method further comprises: grading the active material and then purifying it.
[0041] In some embodiments, the fractionation process comprises airflow fractionation process.
[0042] In some embodiments, the silicon-based material has a median particle size of 2.0 μm to 10.0 μm.
[0043] In some embodiments, the purification step includes washing and drying the silicon-based material after the classification process in a solvent.
[0044] In some embodiments, the purification step includes washing and drying the graded silicon-based material in a solvent, wherein the solvent includes at least one of ethanol, acetone, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and ethylene glycol dimethyl ether.
[0045] In some embodiments, the purification step includes washing and drying the silicon-based material after the classification process in a solvent, and the washing time is 2 hours to 10 hours.
[0046] In some embodiments, the purification step includes washing and drying the graded silicon-based material in a solvent, and the drying temperature is 45°C to 80°C.
[0047] In some embodiments, the purification step includes washing and drying the graded silicon-based material in a solvent, and the drying time is 3 hours to 48 hours.
[0048] In some embodiments, the raw material of the gaseous carbon source includes at least one of methane, ethane, ethylene, acetylene, propyne, propylene, propane, formaldehyde, acetaldehyde, methanol, toluene, benzene, styrene and phenol.
[0049] In some embodiments, the flow rate of the gas-phase carbon source is 200 mL / min to 5000 mL / min.
[0050] In some embodiments, the vapor deposition temperature is 400°C to 1200°C.
[0051] In some embodiments, the vapor deposition time is 1 h to 24 h.
[0052] In some embodiments, the deposition pressure of the vapor deposition is 10 KPa to 0.1 MPa.
[0053] In some embodiments, an auxiliary carrier gas is added during the vapor deposition process.
[0054] In some embodiments, an auxiliary carrier gas is further added during the vapor deposition process, and the auxiliary carrier gas includes at least one of H2, CO2, NH3 and Ar.
[0055] In some embodiments, an auxiliary carrier gas is further added during the vapor deposition process, and the flow rate of the auxiliary carrier gas is 100 mL / min to 8000 mL / min.
[0056] In some embodiments, an auxiliary carrier gas is further added during the vapor deposition process, and the flow ratio of the vapor-phase carbon source to the auxiliary carrier gas is (3-9.5): (0.5-7).
[0057] In some embodiments, the vapor deposition is performed in a deposition chamber of a vapor deposition device, and the rotation speed of the deposition chamber is 0.1 r / min to 10 r / min.
[0058] In some embodiments, the solid phase coating agent includes tetracarboxylic anhydride, copper phthalocyanine, substituted or unsubstituted naphthalene, substituted or unsubstituted anthracene, substituted or unsubstituted phenanthrene, substituted or unsubstituted pyrene, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, C 60 and at least one of substituted or unsubstituted phenalene.
[0059] In some embodiments, the liquid phase capping agent includes at least one of toluene, xylene, styrene, or butyltoluene.
[0060] In some embodiments, the method further comprises classifying and drying the vapor-deposited reaction product, wherein the drying temperature is 50° C. to 120° C.
[0061] In some embodiments, the method further comprises classifying and drying the vapor-deposited reaction product, and the drying time is 6.0 hours to 48.0 hours.
[0062] In some embodiments, the method further comprises: solid-phase mixing or liquid-phase mixing the vapor-deposited product with a coating material, wherein the coating material comprises at least one of nitrides, metal oxides, phosphates and silicates.
[0063] In some embodiments, the step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture comprising the vapor-deposited product and the coating material.
[0064] In some embodiments, the step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture comprising the vapor-deposited product and the coating material, wherein the grinding time is 0.5 h to 48 h.
[0065] In some embodiments, the step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture comprising the vapor-deposited product and the coating material, the heat treatment temperature is 400°C to 1000°C, and the heat treatment time is 1.0h to 24.0h.
[0066] In some embodiments, the step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture comprising the vapor-deposited product and the coating material, wherein the heat treatment is performed under a protective atmosphere, and the protective atmosphere comprises at least one of nitrogen, helium, argon, neon, and krypton.
[0067] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase comprises: drying and heat treating a mixed coating liquid comprising the vapor-deposited product and the coating material;
[0068] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat-treating a mixed coating liquid containing the vapor-deposited product and the coating material; wherein the mixed coating liquid includes a polar solvent.
[0069] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat-treating the mixed coating liquid containing the vapor-deposited product and the coating material; wherein the polar solvent includes at least one of water, anhydrous ethanol, methanol and isopropanol.
[0070] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat-treating the mixed coating liquid containing the vapor-deposited product and the coating material, the drying temperature is 50°C to 120°C, and the time is 6h to 48h.
[0071] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat treating the mixed coating liquid containing the vapor-deposited product and the coating material, the heat treatment temperature is 80°C to 150°C, and the heat treatment time is 3.0h to 48h.
[0072] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat treating the mixed coating liquid containing the vapor-deposited product and the coating material, wherein the heat treatment is carried out under a protective atmosphere, and the protective atmosphere includes at least one of nitrogen, helium, argon, neon, and krypton.
[0073] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the method for preparing the negative electrode material described in the second aspect.
[0074] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:
[0075] The negative electrode material provided in the present application includes a silicon-based material, a coating layer located on the surface of the silicon-based material, the material of the coating layer includes a carbon material, the coating layer can effectively isolate the silicon-based material from exposure to the electrolyte, reduce the loss of active silicon and active lithium in the silicon-based material, and improve the cycle performance of the negative electrode material. The silicon-based material includes silicon oxide and lithium silicate, that is, the surface of the silicon oxide can have a combination of multiple surface substances such as lithium silicate and carbon material; after the negative electrode material is made into a slurry, a nano-particle size and Zeta potential analyzer is used to perform a Zeta potential test on the slurry. In the Zeta potential test distribution diagram of the slurry, I1, I2 and I3 respectively represent the carbon The surface state of the negative electrode material is composed of three substances: lithium silicate and silicon oxide, and when the relationship between I1, I2 and I3 satisfies: 0≤I2 / I1≤2.0, 0≤I3 / I1≤1.0, the surface interface of the negative electrode material has a variety of different surface combinations, the negative electrode material has good interface reaction, and can build a high-speed mass transfer and charge transfer interface between the negative electrode material and the electrolyte, which can improve the mass-charge conduction efficiency, thereby improving the rate performance of the negative electrode material, and forming a stable SEI interface by controlling the solid-liquid reaction between the surface of the negative electrode material and the electrolyte, reducing the degradation of the electrolyte, and inhibiting the cycle expansion, thereby improving the cycle performance of the negative electrode material.
[0076] The negative electrode material preparation method provided in the present application prepares the negative electrode material by vapor-depositing the silicon-based material with a gas-phase carbon source, and simultaneously adding a solid-phase coating agent and / or a liquid-phase coating agent for vapor-phase deposition. During the vapor-phase deposition process, since different carbon sources have different dissociation efficiencies at the same temperature, the deposition efficiencies on the surface of the silicon-based material are also different. Different types of carbon sources are deposited on the surface of the silicon-based material in sequence, thereby forming a differentiated deposition on the surface of the silicon-based material. The carbon material formed by the dissociation of the gas-phase carbon source is deposited on the surface of the silicon-based material to form a coating layer. At the same time, the solid-phase coating agent The carbon material formed by the dissociation of the solid-phase coating agent and / or the liquid-phase coating agent will be deposited into the coating layer and buried in the coating layer. Since the solid-phase coating agent and / or the liquid-phase coating agent contain a benzene ring structure, which is mainly derived from aromatic low-melting and boiling point organic matter, these organic matter can further perform surface modification and functional doping on the coating layer during the carbonization process, thereby optimizing the surface of the coating layer of the negative electrode material, further enriching the surface interface of the negative electrode material, and realizing the regulation of the surface interface of the negative electrode material, thereby controlling the surface interface reaction of the negative electrode material and improving the processing performance and cycle performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0078] Figure 1 A process flow chart of a method for preparing a negative electrode material provided in an embodiment of the present application;
[0079] Figure 2 This is a Zeta potential test distribution diagram of the negative electrode material provided in Example 1 of the present application;
[0080] Figure 3 This is a Zeta potential test distribution diagram of the negative electrode material provided in Example 2 of the present application;
[0081] Figure 4 This is a Zeta potential test distribution diagram of the negative electrode material provided in Example 3 of the present application;
[0082] Figure 5 This is a Zeta potential test distribution diagram of the negative electrode material provided in Example 4 of the present application;
[0083] Figure 6 This is a Zeta potential test distribution diagram of the negative electrode material provided in Example 5 of the present application;
[0084] Figure 7 Zeta potential test distribution diagram of the negative electrode material provided in Comparative Example 1 of the present application;
[0085] Figure 8 This is the Zeta potential test distribution diagram of the negative electrode material provided in Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0086] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0087] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0088] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0089] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0090] In a first aspect, an embodiment of the present application provides a negative electrode material, the negative electrode material comprising a silicon-based material and a coating layer located on at least a portion of the surface of the silicon-based material, the silicon-based material comprising silicon oxide and lithium silicate, and the material of the coating layer comprising a carbon material;
[0091] 20 mg of the negative electrode material is dissolved in 10 ml of deionized water to form a slurry, and the slurry is subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the negative electrode slurry, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50 mV to -40 mV is I1, the maximum intensity of the second characteristic peak in the Zeta potential range of -65 mV to -50 mV is I2, and the maximum intensity of the third characteristic peak in the Zeta potential range of -35 mV to -25 mV is I3, and the relationship between I1, I2, and I3 satisfies: 0≤I2 / I1≤2.0, 0≤I3 / I1≤1.0.
[0092] The negative electrode material provided in the present application includes a silicon-based material, a coating layer located on the surface of the silicon-based material, the material of the coating layer includes a carbon material, the coating layer can effectively isolate the silicon-based material from exposure to the electrolyte, reduce the loss of active silicon and active lithium in the silicon-based material, and improve the cycle performance of the negative electrode material. The silicon-based material includes silicon oxide and lithium silicate, that is, the surface of the silicon oxide can have a combination of multiple surface substances such as lithium silicate and carbon material; after the negative electrode material is made into a slurry, a nano-particle size and Zeta potential analyzer is used to perform a Zeta potential test on the slurry. In the Zeta potential test distribution diagram of the slurry, I1, I2 and I3 respectively represent the carbon The surface state of the negative electrode material is composed of three substances: lithium silicate and silicon oxide, and when the relationship between I1, I2 and I3 satisfies: 0≤I2 / I1≤2.0, 0≤I3 / I1≤1.0, the surface interface of the negative electrode material has a variety of different surface combinations, the negative electrode material has good interface reaction, and can build a high-speed mass transfer and charge transfer interface between the negative electrode material and the electrolyte, which can improve the mass-charge conduction efficiency, thereby improving the rate performance of the negative electrode material, and forming a stable SEI interface by controlling the solid-liquid reaction between the surface of the negative electrode material and the electrolyte, reducing the degradation of the electrolyte, and inhibiting the cycle expansion, thereby improving the cycle performance of the negative electrode material.
[0093] Specifically, I2 / I1 can be, for example, 0, 0.1, 0.3, 0.5, 0.7, 0.8, 0.9, 1.0, 1.1, 1.3, 1.5, 1.7, 1.8 or 2.0, etc., which are not limited here. It should be noted that when I2 is 0, that is, the surface ratio of lithium silicate in the surface interface of the negative electrode material is 0, indicating that the active material is completely coated with carbon material. I3 / I1 can be 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, etc., which are not limited here.
[0094] Understandably, when the ratio of I2 / I1 is greater than 2, the rationality of the surface charge ion distribution of the negative electrode material decreases, and the surface interface of the negative electrode material tends from diversified to single, so that the slurry dispersion of the negative electrode material decreases and the slurry produces gas due to the change of zeta potential during the slurry adjustment process, and the negative electrode material electrolyte will be excessively degraded and deposited in the electrochemical reaction, causing the pole piece to expand, and then affecting the safety and cycle performance of the lithium-ion battery. Controlling the ratio of I2 / I1 within the above range can make the surface interface potential distribution of the negative electrode material reasonable, so that the surface interface of the negative electrode material has diversified characteristics. On the one hand, it can realize solid-liquid regulation of the negative electrode material during the slurry adjustment process, inhibit gas production, and improve the dispersion of the slurry; on the other hand, in the electrochemical reaction, it can regulate the degradation reaction and deposition mode with the electrolyte, stabilize the SEI interface, and alleviate the volume expansion of the material, thereby improving the cycle performance of the negative electrode material and maximizing the electrochemical performance of the negative electrode material. In addition, by controlling the ratio of I2 / I1, the surface composition of the negative electrode material can be regulated. By regulating the surface of the negative electrode material, a fast ion electron transmission channel can be established, the conductivity of the negative electrode material can be improved, the material rate performance can be enhanced, and the loss of active silicon and active lithium can be reduced.
[0095] In some embodiments, the carbon material includes at least one of graphite, amorphous carbon, diamond-like carbon, carbon fiber, and carbide.
[0096] In some embodiments, amorphous carbon includes soft carbon and hard carbon.
[0097] In some embodiments, the carbon material includes silicon carbide.
[0098] In some embodiments, the material of the coating layer further includes at least one of nitride, metal oxide, phosphate and silicate.
[0099] In some embodiments, the material of the coating layer further includes nitride, and the nitride includes at least one of silicon nitride, pyrrole, and pyridine.
[0100] In some embodiments, the material of the coating layer further comprises a metal oxide, and the metal oxide comprises at least one of titanium oxide, aluminum oxide, magnesium oxide, lithium oxide, zirconium oxide, cobalt oxide and vanadium oxide.
[0101] In some embodiments, the material of the coating layer also includes phosphate, and the phosphate includes at least one of lithium phosphate, aluminum phosphate, lithium aluminum phosphate, lithium titanium aluminum phosphate, magnesium phosphate, lithium magnesium phosphate, calcium phosphate, lithium calcium phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and triammonium phosphate.
[0102] In some embodiments, the material of the coating layer further includes silicate, and the silicate includes at least one of lithium silicate, magnesium silicate, aluminum silicate, magnesium aluminum silicate, lithium magnesium silicate, calcium silicate, magnesium calcium silicate, lithium calcium silicate or lithium aluminum silicate.
[0103] In some embodiments, the thickness of the coating layer is 20nm to 700nm, specifically 20nm, 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm or 700nm, etc., and of course, other values within the above range can also be used, which are not limited here. If the coating layer is too thick, the lithium ion transmission efficiency is reduced, which is not conducive to high-rate charge and discharge of the material, and reduces the comprehensive performance of the negative electrode material. If the coating layer is too thin, it is not conducive to increasing the conductivity of the negative electrode material and has weak inhibition performance on the volume expansion of the material, resulting in poor long-cycle performance.
[0104] In some embodiments, the silicon oxide comprises oxygen atoms and silicon atoms, and the molar ratio of oxygen atoms to silicon atoms is 0.5 to 2. The silicon oxide can be represented by the general formula SiO x (0.5≤x≤2). It can be a material formed by silicon particles dispersed in SiO2, or a material having a tetrahedral structural unit, in which the silicon atom is located at the center of the tetrahedral structural unit, and the silicon atom and the oxygen atom are located at the four vertices of the tetrahedral structural unit.
[0105] In some embodiments, the median particle size of the silicon-based material is 2.0 μm to 10.0 μm, specifically 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm or 10.0 μm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0106] In some embodiments, the lithium content in the silicon-based material is 10 3 ppm~10 5ppm, specifically can be 1000ppm, 2000ppm, 5000ppm, 10000ppm, 30000ppm, 50000ppm, 80000ppm or 100000ppm, etc., of course, it can also be other values within the above range, which is not limited here.
[0107] In some embodiments, the general formula of the lithium silicate is Li2O-nSiO2, wherein 0<n≤4. Specifically, the value of n can be 0.5, 1, 1.5, 2, 2.5, 3, 3.5 or 4, etc., which are not limited here. Exemplarily, when the value of n is 1, the lithium silicate is Li2O·SiO2, and when the value of n is 2, the lithium silicate is Li2O-2SiO2, which will not be described in detail here.
[0108] In some embodiments, the lithium silicate is located on at least a portion of the surface of the silicon oxide, and the lithium silicate is dispersed on the surface of the silicon oxide.
[0109] In some embodiments, the median particle size of the negative electrode material is 2 μm to 12 μm. Specifically, the median particle size of the negative electrode material can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm, etc., which is not limited here. The median particle size of the negative electrode material is controlled within the above range, which is conducive to the improvement of the cycle performance of the negative electrode material. Preferably, the median particle size of the negative electrode material is 2.0 μm to 9.0 μm.
[0110] In some embodiments, the specific surface area of the negative electrode material is 0.5 m 2 / g~8.0m 2 / g, specifically 0.5m 2 / g, 1.0m 2 / g, 2.0m 2 / g, 3.0m 2 / g, 4.0m 2 / g, 5.0m 2 / g, 6.0m 2 / g, 7.0m 2 / g or 8.0m 2 / g, of course, it can also be other values within the above range, which is not limited here. The specific surface area of the negative electrode material is within the above range, which ensures the processing performance of the material, is conducive to improving the initial efficiency of the lithium battery made of the negative electrode material, and is conducive to improving the cycle performance of the negative electrode material. Preferably, the specific surface area of the negative electrode material is 1.0m 2 / g~4.0m 2 / g.
[0111] In some embodiments, the tap density of the negative electrode material is 0.5 g / cm3 ~2.0g / cm 3 , specifically 0.5g / cm 3 , 0.7g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 or 2.0g / cm 3 Of course, it can also be other values within the above range, which is not limited here. The tap density of the negative electrode material is within the above range, which is conducive to improving the energy density of the lithium battery made of the negative electrode material. Preferably, the tap density of the negative electrode material is 0.7g / cm 3 ~1.6g / cm 3 .
[0112] In some embodiments, the mass content of water in the negative electrode material is 0.01% to 0.5%, specifically 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, and of course it can also be other values within the above range, which is not limited here.
[0113] In some embodiments, based on the mass of the negative electrode material being 100%, the mass proportion of the carbon material is 0.5wt% to 10wt%, specifically 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., and of course, other values within the above range may also be used, which are not limited here. Preferably, the mass proportion of the carbon material in the negative electrode material is 2.5wt% to 8wt%.
[0114] In some embodiments, based on the mass of the negative electrode material as 100%, the lithium content in the negative electrode material is 2% to 15%, specifically 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc., and of course it can also be other values within the above range, which is not limited here.
[0115] In some embodiments, the pH of the negative electrode material is 10.0-12.3, specifically 10.0, 10.3, 10.5, 10.8, 11.0, 11.2, 11.5, 11.7, 11.9, 12.0, 12.1, 12.2 or 12.3, and certainly other values within the above range are also possible, which are not limited here.
[0116] In a second aspect, the present application provides a method for preparing a negative electrode material, such as Figure 1 As shown, the following steps are included:
[0117] Step S100, providing a pre-lithiation silicon-based material, wherein the silicon-based material includes silicon oxide and lithium silicate;
[0118] Step S200, using a gas-phase carbon source to perform vapor phase deposition on the pre-lithiation silicon-based material, and at the same time adding a solid-phase coating agent and / or a liquid-phase coating agent for vapor phase deposition to obtain a negative electrode material, wherein the negative electrode material includes a silicon-based material and a coating layer located on at least a portion of the surface of the silicon-based material, the coating layer includes a carbon material formed by the deposition of the solid-phase coating agent and / or the liquid-phase coating agent and a carbon material formed by the deposition of the gas-phase carbon source, and the solid-phase coating agent and / or the liquid-phase coating agent contain a benzene ring structure.
[0119] The negative electrode material preparation method provided in the present application prepares the negative electrode material by vapor-depositing the silicon-based material with a gas-phase carbon source, and simultaneously adding a solid-phase coating agent and / or a liquid-phase coating agent for vapor-phase deposition. During the vapor-phase deposition process, since different carbon sources have different dissociation efficiencies at the same temperature, the deposition efficiencies on the surface of the silicon-based material are also different. Different types of carbon sources are deposited on the surface of the silicon-based material in sequence, thereby forming a differentiated deposition on the surface of the silicon-based material. The carbon material formed by the dissociation of the gas-phase carbon source is deposited on the surface of the silicon-based material to form a coating layer. At the same time, the solid-phase coating agent The carbon material formed by the dissociation of the solid-phase coating agent and / or the liquid-phase coating agent will be deposited into the coating layer and buried in the coating layer. Since the solid-phase coating agent and / or the liquid-phase coating agent contain a benzene ring structure, which is mainly derived from aromatic low-melting and boiling point organic matter, these organic matter can further perform surface modification and functional doping on the coating layer during the carbonization process, thereby optimizing the surface of the coating layer of the negative electrode material, further enriching the surface interface of the negative electrode material, and realizing the regulation of the surface interface of the negative electrode material, thereby controlling the surface interface reaction of the negative electrode material and improving the processing performance and cycle performance of the negative electrode material.
[0120] The following is a detailed description of the preparation method provided in this scheme:
[0121] Step S100, providing a pre-lithiation silicon-based material, wherein the silicon-based material includes silicon oxide and lithium silicate.
[0122] In some embodiments, the step of providing a pre-lithiation silicon-based material comprises: performing a pre-physical and chemical treatment on a mixture comprising silicon oxide and a lithium source to obtain the pre-lithiation silicon-based material.
[0123] In some embodiments, the silicon oxide is silicon monoxide.
[0124] In some embodiments, the lithium source includes at least one of lithium hydride, alkyl lithium, metallic lithium, lithium aluminum hydride, lithium amide, lithium borohydride, and silicon-lithium alloy.
[0125] In some embodiments, the mass ratio of the silicon oxide to the lithium source is (85-99):(1-15), specifically 85:15, 88:12, 90:10, 92:8, 95:5, 96:4, 97:3, 98:2 or 99:1, etc. Of course, it can also be other values within the above range, which is not limited here.
[0126] In some embodiments, the pre-treatment time is 0.5h to 24.0h, specifically 0.5h, 1h, 3h, 5h, 8h, 10h, 12h, 15h, 18h, 20h or 24h, etc. Of course, it can also be other values within the above range, which is not limited here.
[0127] In some embodiments, the temperature of the pre-treatment is 300°C to 1000°C, specifically 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0128] In some embodiments, the pre-chemical treatment is performed under an inert gas atmosphere, and the inert gas atmosphere includes at least one of helium, neon, argon, krypton and xenon.
[0129] In some embodiments, before subjecting the mixture comprising silicon oxide and lithium source to pre-physical and chemical treatment, the method further comprises: subjecting the silicon oxide and lithium source to shaping treatment after mixing them to obtain the mixture comprising silicon oxide and lithium source.
[0130] In some embodiments, before subjecting the mixture comprising silicon oxide and a lithium source to a pre-physical and chemical treatment, the method further comprises: mixing the silicon oxide and the lithium source and then subjecting the mixture to a shaping treatment to obtain a mixture comprising silicon oxide and a lithium source, wherein the shaping treatment comprises at least one of crushing, ball milling, grinding and gas crushing.
[0131] In some embodiments, before vapor-depositing the silicon-based material using a vapor-phase carbon source, the method further comprises: subjecting the silicon-based material to a grading treatment and then a purification treatment.
[0132] It can be understood that grading the silicon-based materials can control the particle size range of the silicon-based materials. By controlling the particle size of the silicon-based materials, the specific surface area and the outer surface modification surface of the silicon-based materials can be effectively regulated, which is beneficial to control the deposition efficiency of the negative electrode material and to control the construction of the diversified surface of the material. Purifying the active substances can form a differentiated adsorption interface on the outer surface of the active substances, so that the coating layer can form a differentiated deposition during the deposition process, thereby regulating the surface interface, realizing surface interface synthesis regulation, and realizing the synthesis of the preferred surface interface.
[0133] In some embodiments, the fractionation process comprises airflow fractionation process.
[0134] In some embodiments, the median particle size of the silicon-based material is 2.0 μm to 10.0 μm, specifically 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm or 10.0 μm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0135] In some embodiments, the purification step includes washing and drying the silicon-based material after the classification process in a solvent.
[0136] In some embodiments, the purification step includes washing and drying the graded silicon-based material in a solvent, wherein the solvent includes at least one of ethanol, acetone, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and ethylene glycol dimethyl ether.
[0137] In some embodiments, the purification step includes washing and drying the graded silicon-based material in a solvent, and the washing time is 2 hours to 10 hours. The washing time can be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, etc., which is not limited here.
[0138] In some embodiments, the purification step includes washing and drying the graded silicon-based material in a solvent, and the drying temperature is 45°C to 80°C, specifically 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0139] In some embodiments, the purification step includes washing and drying the graded silicon-based material in a solvent, and the drying time is 3 h to 48 h, specifically 3 h, 5 h, 10 h, 12 h, 15 h, 18 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h or 48 h, etc., and of course, it can also be other values within the above range, which is not limited here.
[0140] Step S200, using a gas-phase carbon source to perform vapor deposition on the silicon-based material, and simultaneously adding a solid-phase coating agent and / or a liquid-phase coating agent for vapor deposition to obtain a negative electrode material, wherein the negative electrode material includes a silicon-based material and a coating layer located on at least a portion of the surface of the silicon-based material, the coating layer includes a carbon material formed by the deposition of the solid-phase coating agent and / or the liquid-phase coating agent and a carbon material formed by the deposition of the gas-phase carbon source, and the solid-phase coating agent and / or the liquid-phase coating agent contain a benzene ring structure.
[0141] In some embodiments, the raw material of the gaseous carbon source includes at least one of methane, ethane, ethylene, acetylene, propyne, propylene, propane, formaldehyde, acetaldehyde, methanol, toluene, benzene, styrene and phenol.
[0142] In some embodiments, the flow rate of the gaseous carbon source is 200 mL / min to 5000 mL / min, specifically 200 mL / min, 500 mL / min, 800 mL / min, 1000 mL / min, 2000 mL / min, 3000 mL / min, 4000 mL / min, 4500 mL / min or 5000 mL / min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0143] In some embodiments, the deposition temperature of the vapor deposition is 400°C to 1200°C, specifically 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C or 1200°C, etc. Of course, it can also be other values within the above range, which are not limited here. Controlling the deposition temperature within the above range can control the cracking efficiency of the gas phase carbon source, thereby regulating the deposition efficiency of the carbon material on the surface of the negative electrode active material; at the same time, it can also control the volatilization efficiency of the solid phase coating agent and the liquid phase coating agent, as well as the functional group retention efficiency. Controlling the deposition temperature within this temperature range can ensure that the size of the silicon grains is controlled within a certain range, while also ensuring the degree of carbonization of the negative electrode material, reducing the proportion of CH bonds in the negative electrode material, and increasing the conductivity of the carbon coating layer, thereby improving the conductivity of the negative electrode material.
[0144] In some embodiments, the deposition time of the vapor deposition is 1 h to 24 h. Specifically, the deposition time of the vapor deposition can be 1 h, 3 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h or 24 h, etc., which is not limited here. It can be understood that if the deposition time of the vapor deposition is too long, it is easy to cause the coating layer to be too thick, and if the deposition time of the vapor deposition is too short, it is easy to cause the coating layer to be too thick. Controlling the deposition time within the above range can control the thickness of the coating layer, which is conducive to controlling the thickness of the coating layer within the ideal range.
[0145] In some embodiments, the deposition pressure of the vapor deposition is 10KPa to 0.1MPa, and specifically can be 10KPa, 20KPa, 30KPa, 40KPa, 50KPa, 60KPa, 70KPa, 80KPa, 90KPa or 0.1MPa, etc., which are not limited here. Controlling the deposition pressure within the above range can control the compactness of the coating layer, so that the coating layer has good compactness, improve the stability of the negative electrode material, and thus improve the cycle performance of the negative electrode material.
[0146] In some embodiments, an auxiliary carrier gas is also added during the vapor deposition process. It can be understood that the auxiliary carrier gas can be used to bring the solid-phase coating agent and / or the liquid-phase coating agent into the vapor deposition furnace for vapor deposition, and the solid-phase coating agent and / or the liquid-phase coating agent can be deposited into the coating layer during the deposition process, and the coating layer of the negative electrode material is surface modified and functionally doped, so as to achieve surface interface optimization, further enrich the surface interface of the negative electrode material, and realize the regulation of the material surface interface; at the same time, the auxiliary carrier gas can also accelerate the cracking of the carbon source, increase the cracking rate of the carbon source and the rate of vapor deposition; the auxiliary carrier gas can increase the terminal structure of the carbon chain, so that different types of carbon materials are deposited on the surface of the negative electrode material, and the pore environment of the negative electrode material is optimized.
[0147] In some embodiments, an auxiliary carrier gas is further added during the vapor deposition process, and the auxiliary carrier gas includes at least one of H2, CO2, NH3 and Ar.
[0148] In some embodiments, an auxiliary carrier gas is added during the vapor deposition process, and the flow rate of the auxiliary carrier gas is 100mL / min to 8000mL / min, specifically 100mL / min, 500mL / min, 1000mL / min, 2000mL / min, 3000mL / min, 4000mL / min, 5000mL / min, 6000mL / min, 7000mL / min or 8000mL / min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0149] In some embodiments, an auxiliary carrier gas is also added during the vapor deposition process, and the flow ratio of the gas-phase carbon source to the auxiliary carrier gas is (3-9.5): (0.5-7), specifically 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1 or 9.5:0.5, etc. Of course, it can also be other values within the above range, which is not limited here.
[0150] In some embodiments, an auxiliary carrier gas is also added during the vapor deposition process, and the volume ratio of the gas-phase carbon source to the auxiliary carrier gas is (3-9.5): (0.5-7), specifically 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, 9:1 or 9.5:0.5, etc. Of course, it can also be other values within the above range, which is not limited here.
[0151] In some embodiments, the vapor deposition is carried out in a deposition chamber of a vapor deposition device, and the rotation speed of the deposition chamber is 0.1 r / min to 10 r / min, specifically 0.1 r / min, 0.5 r / min, 1 r / min, 2 r / min, 3 r / min, 4 r / min, 5 r / min, 6 r / min, 7 r / min, 8 r / min, 9 r / min or 10 r / min, etc., and of course, other values within the above range can also be used, which are not limited here. Controlling the rotation speed of the deposition chamber within the above range is conducive to improving the uniformity of deposition and coating between the negative electrode material particles.
[0152] In some embodiments, the solid phase coating agent includes tetracarboxylic anhydride, copper phthalocyanine, substituted or unsubstituted naphthalene, substituted or unsubstituted anthracene, substituted or unsubstituted phenanthrene, substituted or unsubstituted pyrene, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, C 60 Or at least one of substituted or unsubstituted phenalene.
[0153] In some embodiments, the liquid phase capping agent includes at least one of toluene, xylene, styrene, ethylene glycol dimethyl ether, or butyltoluene.
[0154] In some embodiments, the method further comprises classifying and drying the vapor-deposited reaction product.
[0155] It can be understood that the classification of the reaction product of the vapor deposition can break up the powder agglomeration of the negative electrode material, and at the same time help control the median particle size of the negative electrode material within a preferred range. Drying the reaction product of the vapor deposition can remove moisture from the negative electrode material, thereby helping to improve the electrochemical performance of the negative electrode material.
[0156] In some embodiments, the median particle size of the negative electrode material is 2 μm to 12 μm. Specifically, the median particle size of the negative electrode material can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm, etc., which are not limited here. Preferably, the median particle size of the negative electrode material is 2 μm to 9 μm.
[0157] In some embodiments, the drying temperature is 50°C to 120°C, specifically 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C or 120°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0158] In some embodiments, the drying time is 6.0 h to 48.0 h, specifically 6 h, 12 h, 15 h, 18 h, 20 h, 24 h, 30 h, 36 h, 40 h, 45 h or 48 h, etc. Of course, it can also be other values within the above range, which is not limited here.
[0159] In some embodiments, the method further comprises: solid-phase mixing or liquid-phase mixing the vapor-deposited product with a coating material, wherein the coating material comprises at least one of nitrides, metal oxides, phosphates and silicates.
[0160] In some embodiments, the step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture comprising the vapor-deposited product and the coating material.
[0161] In some embodiments, the step of solid-phase mixing the vapor-deposited product with the coating material includes: grinding and heat treating the mixture containing the vapor-deposited product and the coating material, and the grinding time is 0.5h to 48h, specifically 0.5h, 1h, 3h, 8h, 12h, 15h, 18h, 24h, 36h, 40h, 45h or 48h, etc., which is not limited here.
[0162] In some embodiments, the step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture comprising the vapor-deposited product and the coating material, the heat treatment temperature is 400°C to 1000°C, and the heat treatment time is 1.0h to 24.0h.
[0163] Specifically, the heat treatment temperature may be 400°C, 450°C, 500°C, 600°C, 800°C, 900°C or 1000°C, etc., and is not limited here. The heat treatment time may be 1h, 3h, 5h, 8h, 12h, 15h, 18h, 20h or 24h, etc., and is not limited here.
[0164] In some embodiments, the step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture comprising the vapor-deposited product and the coating material, wherein the heat treatment is performed under a protective atmosphere, and the protective atmosphere comprises at least one of nitrogen, helium, argon, neon, and krypton.
[0165] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat-treating a mixed coating liquid containing the vapor-deposited product and the coating material.
[0166] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat-treating a mixed coating liquid containing the vapor-deposited product and the coating material; wherein the mixed coating liquid includes a polar solvent.
[0167] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat-treating the mixed coating liquid containing the vapor-deposited product and the coating material; wherein the polar solvent includes at least one of water, anhydrous ethanol, methanol and isopropanol.
[0168] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat-treating the mixed coating liquid containing the vapor-deposited product and the coating material, the drying temperature is 50°C to 120°C, and the time is 6h to 48h.
[0169] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat treating the mixed coating liquid containing the vapor-deposited product and the coating material, the heat treatment temperature is 80°C to 150°C, and the heat treatment time is 3.0h to 48.0h.
[0170] Specifically, the temperature of the heat treatment may be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, etc., which is not limited here. The time of the heat treatment may be 3h, 5h, 8h, 12h, 15h, 18h, 24h, 30h, 36h, 45h or 48h, etc., which is not limited here.
[0171] In some embodiments, the step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat treating the mixed coating liquid containing the vapor-deposited product and the coating material, wherein the heat treatment is carried out under a protective atmosphere, and the protective atmosphere includes at least one of nitrogen, helium, argon, neon, and krypton.
[0172] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the method for preparing the negative electrode material described in the second aspect.
[0173] Example
[0174] Example 1
[0175] (1) 200 g of lithium hydride and 1800 g of silicon oxide were mixed, and the mixture was placed in a vacuum ball mill for vacuum dry ball milling for 60 min to obtain a mixture containing lithium hydride and silicon oxide; the mixture was then placed in an atmosphere protection heat treatment device, argon gas was introduced, and pre-physical and chemical treatment was performed at 1000° C. for 12 h to obtain a silicon-based material; finally, the silicon-based material was subjected to air flow classification treatment until the median particle size was 5.0 μm.
[0176] (2) Weigh 1000 g of silicon-based material (median particle size of 5.0 μm), rinse with deionized water for 30 min, then wash and soak with ethanol for 3 h, and dry in a vacuum drying oven at 80 °C for 24 h;
[0177] (3) The obtained sample was placed in a deposition chamber of a vapor deposition furnace, and methane, acetylene and ethylene gases with a volume ratio of 1:1:1 were introduced into the deposition chamber at a rate of 1000 ml / min as gaseous carbon sources. At the same time, a solid coating agent tetracarboxylic anhydride (PTCDA) was placed at the front end of the vapor deposition furnace. The pressure in the deposition chamber was regulated by a pressure valve. After the vacuum degree in the reaction chamber was evacuated, Ar was introduced as an auxiliary carrier gas at a rate of 1000 ml / min, and then vapor deposition was performed at 450 ° C for 10 hours, wherein the flow ratio of the gaseous carbon source to Ar was 1:1, the rotation speed of the deposition chamber was 5 r / min, and the deposition pressure was 0.05 MPa;
[0178] (4) After the vapor deposition product is graded, it is placed in a vacuum drying oven at 100° C. for 24 hours to obtain a negative electrode material.
[0179] The negative electrode material prepared in this embodiment includes a silicon-based material and a carbon coating layer located on at least a portion of the surface of the active material, and the silicon-based material includes silicon oxide and lithium silicate.
[0180] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 2 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=78769, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=98739, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=38278, and I2 / I1=1.25, I3 / I1=0.486.
[0181] The median particle size of the negative electrode material is 4.92 μm and the specific surface area is 1.57 m 2 / g, tap density is 0.98g / cm 3 The mass content of carbon element in the negative electrode material is 4.93%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 9.55%, and the mass content of water is 0.21%.
[0182] Example 2
[0183] (1) 200 g of lithium hydride and 1800 g of silicon oxide were mixed, and the mixture was placed in a vacuum ball mill for vacuum dry ball milling for 60 min to obtain a mixture containing lithium hydride and silicon oxide; the mixture was then placed in an atmosphere protection heat treatment device, argon gas was introduced, and pre-physical and chemical treatment was performed at 1000° C. for 12 h to obtain a silicon-based material; finally, the silicon-based material was subjected to air flow classification treatment until the median particle size was 5.0 μm.
[0184] (2) Weigh 1000 g of silicon-based material (median particle size of 5.0 μm), rinse with deionized water for 30 min, then wash and soak with acetone for 3 h, and dry in a vacuum drying oven at 80° C. for 24 h.
[0185] (3) The obtained sample was placed in a deposition chamber of a vapor deposition furnace, and methane gas was introduced into the deposition chamber at 1000 mL / min as a gaseous carbon source. At the same time, a solid-phase coating agent, copper phthalocyanine, was placed at the front end of the vapor deposition furnace. The air pressure in the deposition chamber was regulated by a pressure valve. After the vacuum degree in the reaction chamber was evacuated, Ar and NH3 with a volume ratio of 5:1 were introduced as auxiliary carrier gases at 500 mL / min. Then, vapor deposition was carried out at 500°C for 12 hours, wherein the flow ratio of the gaseous carbon source to the auxiliary carrier gas (Ar and NH3) was 2:1, the rotation speed of the deposition chamber was 5 r / min, and the deposition pressure was 0.03 MPa.
[0186] (4) After the vapor deposition product is graded, it is placed in a vacuum drying oven at 100° C. for 24 hours to obtain a negative electrode material.
[0187] The negative electrode material prepared in this embodiment includes a silicon-based material and a carbon coating layer located on at least a portion of the surface of the silicon-based material, and the silicon-based material includes silicon oxide and lithium silicate.
[0188] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 3 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=179809, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=0, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=36206, and I2 / I1=0, I3 / I1=0.201.
[0189] The median particle size of the negative electrode material is 5.1 μm and the specific surface area is 1.72 m 2 / g, tap density is 0.99g / cm 3 The mass content of carbon element in the negative electrode material is 5.12%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 9.13%, and the mass content of water is 0.11%.
[0190] Example 3
[0191] (1) 160 g of lithium hydride and 1840 g of silicon dioxide were mixed, and the mixture was placed in a vacuum ball mill for vacuum dry ball milling for 60 min to obtain a mixture containing lithium hydride and silicon dioxide; the mixture was then placed in an atmosphere protection heat treatment device, argon gas was introduced, and pre-physical and chemical treatment was performed at 1000° C. for 12 h to obtain a silicon-based material; finally, the silicon-based material was subjected to air flow classification treatment until the median particle size was 5.0 μm.
[0192] (2) Weigh 1000 g of silicon-based material (median particle size of 5.0 μm), rinse with deionized water for 30 min, then wash and soak with N,N-dimethylformamide for 1 h, and dry in a vacuum drying oven at 80 °C for 24 h;
[0193] (3) placing the obtained sample in a deposition chamber of a vapor deposition furnace, introducing methane, acetylene, ethylene and propane gases in a volume ratio of 1:1:1:3 into the deposition chamber at a rate of 1500 mL / min as gaseous carbon sources, placing a liquid coating agent toluene at the front end of the vapor deposition furnace, adjusting the gas pressure in the deposition chamber by a pressure valve, and after the vacuum degree in the reaction chamber is evacuated, introducing Ar and NH3 in a volume ratio of 5:1 as auxiliary carrier gases at a rate of 500 mL / min, and then performing vapor deposition at 800°C for 8 hours, wherein the flow ratio of the gaseous carbon source to the auxiliary carrier gas (Ar and NH3) is 3:1, the rotation speed of the deposition chamber is 5 r / min, and the deposition pressure is normal pressure;
[0194] (4) After the vapor deposition product is graded, it is placed in a vacuum drying oven at 100° C. for 24 hours to obtain a negative electrode material.
[0195] The negative electrode material prepared in this embodiment includes an active substance and a carbon coating layer located on at least a portion of the surface of the silicon-based material, and the silicon-based material includes silicon oxide and lithium silicate.
[0196] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 4 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=97941, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=44480, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=67448, and I2 / I1=0.45, I3 / I1=0.689.
[0197] The median particle size of the negative electrode material is 5.1 μm and the specific surface area is 1.29 m 2 / g, tap density is 0.97g / cm 3 The mass content of carbon element in the negative electrode material is 4.98%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 7.13%, and the mass content of water is 0.17%.
[0198] Example 4
[0199] Different from Example 1, the deposition temperature during the vapor deposition process is 600°C.
[0200] The negative electrode material prepared in this embodiment includes a silicon-based material and a carbon coating layer located on at least a portion of the surface of the silicon-based material, and the silicon-based material includes silicon oxide and lithium silicate.
[0201] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 5 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=159008, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=50380, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=64524, and I2 / I1=0.317, I3 / I1=0.406.
[0202] The median particle size of the negative electrode material is 5.12 μm and the specific surface area is 1.58 m 2 / g, tap density is 1.02g / cm 3 The mass content of carbon element in the negative electrode material is 4.99%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 9.04%, and the mass content of water is 0.21%.
[0203] Example 5
[0204] Different from Example 1, the deposition temperature during the vapor deposition process is 900°C.
[0205] The negative electrode material prepared in this embodiment includes a silicon-based material and a carbon coating layer located on at least a portion of the surface of the silicon-based material, and the active material includes silicon oxide and lithium silicate.
[0206] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 6 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=76042, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=32434, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=23691, and I2 / I1=0.427, I3 / I1=0.312.
[0207] The median particle size of the negative electrode material is 5.0 μm and the specific surface area is 1.49 m 2 / g, tap density is 0.98g / cm 3The mass content of carbon element in the negative electrode material is 5.19%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 9.36%, and the mass content of water is 0.09%.
[0208] Embodiment 6:
[0209] (1) 200 g of lithium hydride and 1800 g of silicon oxide were mixed, and the mixture was placed in a vacuum ball mill for vacuum dry ball milling for 60 min to obtain a mixture containing lithium hydride and silicon oxide; the mixture was then placed in an atmosphere protection heat treatment device, argon gas was introduced, and pre-physical and chemical treatment was performed at 1000° C. for 12 h to obtain a silicon-based material; finally, the silicon-based material was subjected to air flow classification treatment until the median particle size was 5.0 μm.
[0210] (2) Weigh 1000 g of silicon-based material (median particle size of 5.0 μm), rinse with deionized water for 30 min, then wash and soak with acetone for 3 h, and dry in a vacuum drying oven at 80° C. for 24 h.
[0211] (3) The obtained sample is placed in the deposition chamber of the vapor deposition furnace, and the liquid coating agent liquid asphalt is placed at the front end of the vapor deposition furnace. The air pressure in the deposition chamber is regulated by the air pressure valve, and the vacuum degree in the reaction chamber is evacuated. Acetylene gas is introduced into the deposition chamber at a rate of 1000mL / min as a gas phase carbon source, and Ar and NH3 with a volume ratio of 1:3 are introduced into the deposition chamber at a rate of 3000mL / min as auxiliary carrier gases, and then vapor deposition is carried out at 700℃ for 12h, wherein the flow ratio of the gas phase carbon source to the auxiliary carrier gas (Ar and NH3) is 1:3, the rotation speed of the deposition chamber is 5r / min, and the deposition pressure is 0.05MPa.
[0212] (4) After the vapor deposition product is graded, it is placed in a vacuum drying oven at 100° C. for 24 hours to obtain a negative electrode material.
[0213] The negative electrode material prepared in this embodiment includes a silicon-based material and a large amount of nitrogen-doped carbon coating layer located on at least a portion of the surface of the silicon-based material, and the silicon-based material includes silicon oxide and lithium silicate.
[0214] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry, and the slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50 mV to -40 mV was I1=113024, the maximum intensity of the second characteristic peak in the Zeta potential range of -65 mV to -50 mV was I2=89211, the maximum intensity of the third characteristic peak in the Zeta potential range of -35 mV to -25 mV was I3=21157, and I2 / I1=0.789, I3 / I1=0.187.
[0215] The median particle size of the negative electrode material is 5.04 μm and the specific surface area is 1.68 m 2 / g, tap density is 1.03g / cm 3 The mass content of carbon in the negative electrode material is 4.87%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 9.02%, and the mass content of water is 0.19%.
[0216] Example 7
[0217] The difference from Example 2 is:
[0218] Before step (4), the method further includes: weighing 65 g of aluminum chloride and dissolving it in 2000 g of deionized water, stirring for 30 minutes, adding 970 g of the vapor-deposited product after the aluminum chloride is completely dissolved, stirring for 120 minutes, and centrifuging to remove the solvent; and vacuum drying the centrifuged material at 80° C. for 48 hours.
[0219] (5) Drying The dried sample was placed in an argon atmosphere and heat treated at 600° C. for 12 h, and then graded to obtain a negative electrode material.
[0220] The negative electrode material prepared in this embodiment includes a silicon-based material and a coating layer located on at least a portion of the surface of the silicon-based material, the silicon-based material includes silicon oxide and lithium silicate, and the coating layer includes carbon material and aluminum oxide.
[0221] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry, and the slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50 mV to -40 mV was I1=121743, the maximum intensity of the second characteristic peak in the Zeta potential range of -65 mV to -50 mV was I2=0, the maximum intensity of the third characteristic peak in the Zeta potential range of -35 mV to -25 mV was I3=57192, and I2 / I1=0, I3 / I1=0.470.
[0222] The median particle size of the negative electrode material is 4.93 μm and the specific surface area is 2.01 m 2 / g, tap density is 1.01g / cm 3 The mass content of carbon element in the negative electrode material is 0.22%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 9.11%, and the mass content of water is 0.08%.
[0223] Example 8
[0224] The difference from Example 2 is that (4) the vapor deposition product is placed in a vacuum drying oven at 100° C. and dried for 24 h.
[0225] After step (4), the method further includes: weighing 970 g of the dried vapor deposition product and uniformly mixing it with 25 g of aluminum oxide and 5 g of lithium fluoride to form a mixture, placing the mixture in a vacuum ball mill for vacuum dry ball milling for 6 hours, placing the ball-milled mixture in an argon atmosphere at 900° C. for 24 hours, and then performing a grading process to obtain a negative electrode material.
[0226] The negative electrode material prepared in this embodiment includes a silicon-based material and a coating layer located on at least a portion of the surface of the silicon-based material, the silicon-based material includes silicon oxide and lithium silicate, and the coating layer includes lithium silicate and aluminum silicate.
[0227] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry, and the slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50 mV to -40 mV was I1=102959, the maximum intensity of the second characteristic peak in the Zeta potential range of -65 mV to -50 mV was I2=0, the maximum intensity of the third characteristic peak in the Zeta potential range of -35 mV to -25 mV was I3=23009, and I2 / I1=0, I3 / I1=0.223.
[0228] The median particle size of the negative electrode material is 5.00 μm and the specific surface area is 1.91 m 2 / g, tap density is 0.96g / cm 3 The mass content of carbon element in the negative electrode material is 0.18%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 9.01%, and the mass content of water is 0.07%.
[0229] Example 9
[0230] The difference from Example 1 is that in step (1), the silicon-based material is air flow-pulverized to a median particle size of 2.0 μm, and the subsequent operations are the same as in Example 1.
[0231] The negative electrode material prepared in this embodiment includes a silicon-based material and a carbon coating layer located on at least a portion of the surface of the active material, and the silicon-based material includes silicon oxide and lithium silicate.
[0232] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 2 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=63788, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=103392, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=29303, and I2 / I1=1.62, I3 / I1=0.46.
[0233] The median particle size of the negative electrode material is 2.07 μm and the specific surface area is 2.45 m 2 / g, tap density is 1.18g / cm 3 The mass content of carbon element in the negative electrode material is 5.12%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 9.67%, and the mass content of water is 0.17%.
[0234] Example 10
[0235] The difference from Example 1 is that in step (1), the silicon-based material is air flow-pulverized to a median particle size of 10.0 μm, and the subsequent operations are the same as in Example 1.
[0236] The negative electrode material prepared in this embodiment includes a silicon-based material and a carbon coating layer located on at least a portion of the surface of the active material, and the silicon-based material includes silicon oxide and lithium silicate.
[0237] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 2 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=72129, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=2309, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=52118, and I2 / I1=0.03, I3 / I1=0.72.
[0238] The median particle size of the negative electrode material is 9.83 μm and the specific surface area is 1.76 m 2 / g, tap density is 0.98g / cm 3 The mass content of carbon element in the negative electrode material is 4.96%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 9.53%, and the mass content of water is 0.05%.
[0239] Embodiment 11
[0240] The difference from Example 1 is that in step (1), 5 g of metallic lithium and 95 g of silicon dioxide are mixed, and the subsequent operations are the same as in Example 1.
[0241] The negative electrode material prepared in this embodiment includes a silicon-based material and a carbon coating layer located on at least a portion of the surface of the active material, and the silicon-based material includes silicon oxide and lithium silicate.
[0242] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 2 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=55192, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=39180, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=10732, and I2 / I1=0.71, I3 / I1=0.19.
[0243] The median particle size of the negative electrode material is 4.93 μm and the specific surface area is 1.92 m 2 / g, tap density is 0.98g / cm 3The mass content of carbon element in the negative electrode material is 5.10%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 5.02%, and the mass content of water is 0.02%.
[0244] Comparative Example 1
[0245] (1) 200 g of lithium hydride and 1800 g of silicon oxide were mixed, and the mixture was placed in a vacuum ball mill for vacuum dry ball milling for 60 min to obtain a mixture containing lithium hydride and silicon oxide; the mixture was then placed in an atmosphere protection heat treatment device, argon gas was introduced, and pre-physical and chemical treatment was performed at 1000° C. for 12 h to obtain a silicon-based material; finally, the silicon-based material was subjected to air flow classification treatment until the median particle size was 5.0 μm.
[0246] (2) Weigh 1000 g of silicon-based material (median particle size of 5.0 μm), rinse with deionized water for 30 min, and dry in a vacuum drying oven at 100° C. for 24 h to obtain a negative electrode material.
[0247] The negative electrode material prepared in this comparative example includes a silicon-based material, wherein the silicon-based material includes silicon oxide and lithium silicate located on at least a portion of the surface of the silicon oxide.
[0248] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 7 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=1731, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=112791, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=41337, and I2 / I1=65.16, I3 / I1=13.27.
[0249] The median particle size of the negative electrode material is 5.0 μm and the specific surface area is 1.31 m 2 / g, tap density is 0.98g / cm 3 The mass content of carbon element in the negative electrode material is 0.33%. Taking the mass of the negative electrode material as 100%, the mass content of lithium in the negative electrode material is 10.31%, and the mass content of water is 0.32%.
[0250] Comparative Example 2
[0251] (1) 200 g of lithium hydride and 1800 g of silicon oxide were mixed, and the mixture was placed in a vacuum ball mill for vacuum dry ball milling for 60 min to obtain a mixture containing lithium hydride and silicon oxide; the mixture was then placed in an atmosphere protection heat treatment device, argon gas was introduced, and pre-physical and chemical treatment was performed at 1000° C. for 12 h to obtain a silicon-based material; finally, the silicon-based material was subjected to air flow classification treatment until the median particle size was 5.0 μm.
[0252] (2) Weigh 1000 g of silicon-based material (median particle size of 5.0 μm), rinse with deionized water for 30 min, and dry in a vacuum drying oven at 100° C. for 24 h.
[0253] (3) placing the obtained sample in a deposition chamber of a vapor deposition furnace, introducing methane gas into the deposition chamber as a gaseous carbon source, and then performing vapor deposition at 900° C. for 4 h, wherein the rotation speed of the deposition chamber is 5 r / min and the deposition pressure is 0.05 MPa;
[0254] (4) After the vapor deposition product is graded, it is placed in a vacuum drying oven at 100° C. for 24 hours to obtain a negative electrode material.
[0255] The negative electrode material prepared in this comparative example includes a silicon-based material and a carbon coating layer located on at least a portion of the surface of the silicon-based material, and the silicon-based material includes silicon oxide and lithium silicate located on at least a portion of the surface of the silicon oxide.
[0256] 20 mg of the negative electrode material was dissolved in 10 ml of deionized water to form a slurry. The slurry was subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, as shown in FIG. Figure 8 As shown, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50mV to -40mV is I1=43212, the maximum intensity of the second characteristic peak in the Zeta potential range of -65mV to -50mV is I2=132771, the maximum intensity of the third characteristic peak in the Zeta potential range of -35mV to -25mV is I3=34179, and I2 / I1=3.07, I3 / I1=1.26.
[0257] The median particle size of the negative electrode material is 5.0 μm and the tap density is 0.98 g / cm 3 , with a specific surface area of 1.59m 2 / g, the mass content of carbon element in the negative electrode material is 4.54%, based on the mass of the negative electrode material being 100%, the mass content of lithium in the negative electrode material is 9.33%, and the mass content of water is 0.21%.
[0258] Test Method
[0259] (1) Testing method for particle size of negative electrode materials:
[0260] The particle size of the negative electrode material was tested using a Malvern Mastersizer 2000 laser particle size tester to obtain the average particle size.
[0261] (2) Testing method for specific surface area of negative electrode materials:
[0262] The dynamic specific surface area rapid tester JW-DX produced by Beijing Jingwei Gaobo Science and Technology Co., Ltd. is used for testing, and the unit is m2 / g.
[0263] (3) Test method for tap density of negative electrode materials:
[0264] Using a vibrator, weigh a certain amount of sample and vibrate 3000 times at 300 times / min to test the tap density.
[0265] (4) Testing method for water content in negative electrode materials:
[0266] Thermogravimetry was used to test the water content in the negative electrode material. At 250°C, the proportion of the mass lost by the negative electrode material in the total weight was the water content in the negative electrode material.
[0267] (5) Testing method for lithium content in negative electrode materials:
[0268] The lithium content of the negative electrode material is tested using an inductively coupled plasma emission spectrometer (ICP): the negative electrode material is burned at high temperature to remove the carbon element; the burnt product is treated with nitric acid and hydrofluoric acid in turn, and then heated to evaporate the acid, and then hydrochloric acid is added to continue the treatment until it is completely dissolved. Finally, after the volume is fixed, the product is tested using an inductively coupled plasma emission spectrometer.
[0269] (6) Test method for mass content of carbon material in negative electrode material:
[0270] Thermogravimetric analysis was used to test the mass content of carbon material in the negative electrode material.
[0271] (8) Test method for Zeta potential of negative electrode materials:
[0272] 20 mg of negative electrode material was weighed and dissolved in deionized water to form a slurry with a pH of 10.5 to 12. The slurry was tested for Zeta potential using a nanoparticle size and Zeta potential analyzer (DLS, model Malvern Zetasizer Nano ZS90).
[0273] (9) Electrochemical performance test:
[0274] According to the equipment and method in BTRTC / ZY / 01-020 "Button Cell Method Operating Instructions": the negative electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were assembled into button cells for testing, wherein a metal lithium sheet was used as the counter electrode, a PP-PE-PP composite film with a diameter of 19.2 mm was used as the separator, the electrolyte component ratio was EC / EMC / DMC=1:1:1, and the lithium salt (LiPF6) concentration was 1.05 mol / L.
[0275] Test of specific capacity of negative electrode material: Use button battery charging and discharging equipment, 0.1C constant current charging to 10mV, then 0.02C constant current charging to 5mV, 0.1C constant current discharging to 1.5V cut-off;
[0276] Half-battery 50-week cycle test: using button cell charging and discharging equipment, in the first week, 0.1C discharge to 0.01V, 0.01C discharge to 0.01V, 0.01C discharge to 0.005V, 0.1C charge to 1.5V; in the second week, 0.2C discharge to 0.01V, 0.02C discharge to 0.01V, 0.02C discharge to 0.005V, 0.2C charge to 1.5V; in the third week, 0.5C discharge to 0.0 1V, 0.05C discharge in equal steps to 0.01V, 0.05C discharge to 0.005V, 0.5C charge to 1.5V; from the 4th to the 50th week, 1C discharge to 0.01V, 0.1C discharge in equal steps to 0.01V, 0.1C discharge to 0.005V, 1C charge to 1.5V; in the 51st week, 0.1C discharge to 0.01V, 0.01C discharge in equal steps to 0.01V, 0.01C discharge to 0.005V.
[0277] Full battery performance test: The negative electrode material is mixed with graphite to make the capacity of the negative electrode material reach the standard 450mAh / g, and the capacity retention rate of the material is tested at 60°C, and the charge and discharge at 0.2C is tested (2.75~4.2V).
[0278] Table 1 Negative electrode material performance test results
[0279]
[0280]
[0281] As shown in Table 1, in the negative electrode materials prepared in Examples 1 to 8, the surface of the silicon-based material has a coating layer, and the coating layer can effectively isolate the exposure of the silicon-based material in the electrolyte, reduce the loss of active silicon and active lithium in the silicon-based material, and improve the cycle performance of the negative electrode material. The negative electrode material is subjected to a Zeta potential test, and the relationship between the intensities of the characteristic peaks I1, I2, and I3 satisfies 0≤I2 / I1≤2.0, 0≤I3 / I1≤1.0. The surface interface of the negative electrode material has a variety of different surface combinations (that is, the surface interface of the negative electrode material is differentiated and diversified), the negative electrode material has a good interface reaction, and a high-speed mass transfer and charge transfer interface between the negative electrode material and the electrolyte can be built, and the mass-charge conduction efficiency can be improved, thereby improving the rate performance of the negative electrode material, controlling the solid-liquid reaction between the surface of the negative electrode material and the electrolyte, forming a stable SEI interface, reducing the degradation of the electrolyte, and inhibiting the cycle expansion, thereby improving the cycle performance of the negative electrode material.
[0282] The negative electrode material prepared in Comparative Example 1 does not undergo coating treatment on the negative electrode active material, resulting in serious loss of the negative electrode active material during the cycle process, which greatly reduces the cycle performance of the negative electrode material; the ratios of I2 / I1 and I3 / I1 are greatly increased, so that the surface interface of the negative electrode material no longer has a variety of different surface combinations. During the electrochemical reaction, the single surface interface of the negative electrode material is difficult to regulate the degradation reaction of the electrolyte, and the excessive degradation and deposition of the electrolyte causes the electrode sheet to expand, which greatly increases the expansion rate of the electrode sheet, thereby greatly reducing the cycle performance of the negative electrode material; at the same time, excessive degradation of the electrolyte is not conducive to the rapid transmission of lithium ions, increases the lithium ion transmission path, and reduces the lithium ion transmission efficiency, thereby greatly reducing the rate performance of the negative electrode material.
[0283] In the negative electrode material prepared in Comparative Example 2, no solid-phase coating agent and / or liquid-phase coating agent is added to modify and dope the coating layer on the surface. The ratios of I2 / I1 and I3 / I1 in the negative electrode material increase, which reduces the rationality of the surface charge ion distribution of the negative electrode material. The surface interface of the negative electrode material tends to be single from diversified. It is difficult to establish fast ion electron transmission channels through the single surface composition of the negative electrode material. The ion electron transmission channels in the negative electrode material are reduced, and the ion transmission efficiency is reduced, resulting in reduced conductivity of the negative electrode material and reduced rate performance of the negative electrode material. At the same time, it is difficult to regulate the degradation reaction of the electrolyte in the electrochemical reaction through a single surface interface, resulting in excessive degradation of the electrolyte, causing expansion of the electrode sheet, and thus reducing the cycle performance of the negative electrode material.
[0284] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises a silicon-based material and a coating layer located on at least a portion of the surface of the silicon-based material, the silicon-based material comprises silicon oxide and lithium silicate, and the material of the coating layer comprises a carbon material; 20 mg of the negative electrode material is dissolved in 10 ml of deionized water to form a slurry, and the slurry is subjected to a Zeta potential test using a nanoparticle size and Zeta potential analyzer. In the Zeta potential test distribution diagram of the slurry, the maximum intensity of the first characteristic peak of the slurry in the Zeta potential range of -50 mV to -40 mV is I1, the maximum intensity of the second characteristic peak in the Zeta potential range of -65 mV to -50 mV is I2, and the maximum intensity of the third characteristic peak in the Zeta potential range of -35 mV to -25 mV is I3, and the relationship between I1, I2, and I3 satisfies: 0≤I2 / I1≤2.0, 0≤I3 / I1≤1.
0.
2. The negative electrode material according to claim 1, characterized in that The negative electrode material includes at least one of the following features (1) to (8): (1) The carbon material includes at least one of graphite, amorphous carbon, diamond-like carbon, carbon fiber and carbide; (2) The carbon material includes silicon carbide; (3) The material of the coating layer further includes at least one of nitride, metal oxide, phosphate and silicate; (4) The material of the coating layer further includes nitride, and the nitride includes at least one of silicon nitride, pyrrole and pyridine; (5) The material of the coating layer further includes a metal oxide, and the metal oxide includes at least one of titanium oxide, aluminum oxide, magnesium oxide, lithium oxide, zirconium oxide, cobalt oxide and vanadium oxide; (6) The material of the coating layer further includes phosphate, and the phosphate includes at least one of lithium phosphate, aluminum phosphate, lithium aluminum phosphate, lithium titanium aluminum phosphate, magnesium phosphate, lithium magnesium phosphate, calcium phosphate, lithium calcium phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and triammonium phosphate; (7) The material of the coating layer further includes silicate, and the silicate includes at least one of lithium silicate, magnesium silicate, aluminum silicate, magnesium aluminum silicate, lithium magnesium silicate, calcium silicate, magnesium calcium silicate, lithium calcium silicate and lithium aluminum silicate; (8) The thickness of the coating layer is 20 nm to 700 nm.
3. The negative electrode material according to claim 1, characterized in that The negative electrode material includes at least one of the following features (1) to (12): (1) The median particle size of the silicon-based material is 2.0 μm to 10.0 μm; (2) The mass content of lithium in the silicon-based material is 10 3 ppm~10 5 ppm; (3) The general formula of the lithium silicate is Li2O-nSiO2, wherein 0<n≤4; (4) The lithium silicate is located on at least a portion of the surface of the silicon oxide; (5) The lithium silicate is located on at least a portion of the surface of the silicon oxide, and the lithium silicate is dispersed on the surface of the silicon oxide; (6) The median particle size of the negative electrode material is 2 μm to 12 μm; (7) The specific surface area of the negative electrode material is 0.5 m 2 / g~8.0m 2 / g; (8) The tap density of the negative electrode material is 0.5 g / cm 3 ~3.0g / cm 3 ; (9) The mass content of water in the negative electrode material is 0.01% to 0.5%; (10) Based on the mass of the negative electrode material being 100%, the mass of the carbon material accounts for 0.5wt% to 10wt%; (11) Based on the mass of the negative electrode material being 100%, the mass content of lithium in the negative electrode material is 2% to 15%; (12) The pH of the negative electrode material is 10.0 to 12.
3.
4. A method for preparing a negative electrode material, characterized in that: The following steps are involved: Providing a pre-lithium silicon-based material, wherein the silicon-based material comprises silicon oxide and lithium silicate; A gas-phase carbon source is used to perform gas phase deposition on a pre-lithiation silicon-based material, and a solid-phase coating agent and / or a liquid-phase coating agent are simultaneously added for gas phase deposition to obtain a negative electrode material, wherein the negative electrode material comprises a silicon-based material and a coating layer located on at least a portion of the surface of the silicon-based material, the coating layer comprises a carbon material formed by deposition of the solid-phase coating agent and / or the liquid-phase coating agent and a carbon material formed by deposition of the gas-phase carbon source, and the solid-phase coating agent and / or the liquid-phase coating agent contain a benzene ring structure.
5. The preparation method according to claim 4, characterized in that: The step of providing a pre-lithiation silicon-based material comprises: pre-physical and chemically treating a mixture containing silicon oxide and a lithium source to obtain a pre-lithiation silicon-based material; the method comprises at least one of the following features (1) to (8): (1) The silicon oxide is silicon monoxide; (2) The lithium source comprises at least one of lithium hydride, alkyl lithium, metallic lithium, lithium aluminum hydride, lithium amide, lithium borohydride and lithium silicon alloy; (3) The mass ratio of the silicon oxide to the lithium source is (85-99): (15-1); (4) The pre-treatment time is 0.5h to 24.0h; (5) The temperature of the pre-treatment is 300°C to 1000°C; (6) The pre-physical and chemical treatment is carried out in an inert gas atmosphere, wherein the inert gas atmosphere comprises at least one of helium, neon, argon, krypton and xenon; (7) Before subjecting the mixture containing silicon oxide and lithium source to pre-physical and chemical treatment, the method further comprises: mixing the silicon oxide and lithium source and then subjecting the mixture to shaping treatment to obtain the mixture containing silicon oxide and lithium source; (8) Before subjecting the mixture containing silicon oxide and lithium source to pre-physical and chemical treatment, the method further comprises: mixing the silicon oxide and lithium source and then subjecting the mixture to shaping treatment to obtain the mixture containing silicon oxide and lithium source, wherein the shaping treatment comprises at least one of crushing, ball milling, grinding and gas crushing.
6. The preparation method according to claim 4, characterized in that: Before vapor deposition of the silicon-based material using a gas-phase carbon source, the method further comprises: grading the silicon-based material and then purifying it. The method comprises at least one of the following features (1) to (6): (1) The classification process includes airflow classification process; (2) The median particle size of the silicon-based material is 2.0 μm to 10.0 μm; (3) The purification step includes washing and drying the silicon-based material after the classification process in a solvent; (4) The purification step comprises washing and drying the silicon-based material after the classification process in a solvent, wherein the solvent comprises at least one of water, ethanol, acetone, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and ethylene glycol dimethyl ether; (5) The purification step includes washing and drying the silicon-based material after the classification process in a solvent, wherein the washing time is 2 hours to 10 hours; (6) The purification step includes washing and drying the silicon-based material after the classification process in a solvent, wherein the drying temperature is 45° C. to 80° C.; (7) The purification step includes washing and drying the silicon-based material after the classification process in a solvent, and the drying process takes 3 hours to 48 hours.
7. The preparation method according to claim 4, characterized in that: The method comprises at least one of the following features (1) to (10): (1) The raw material of the gaseous carbon source includes at least one of methane, ethane, ethylene, acetylene, propyne, propylene, propane, formaldehyde, acetaldehyde, methanol, toluene, benzene, styrene and phenol; (2) The flow rate of the gas phase carbon source is 200 mL / min to 5000 mL / min; (3) The deposition temperature of the vapor deposition is 400° C. to 1200° C.; (4) The deposition time of the vapor deposition is 1 h to 24 h; (5) The deposition pressure of the vapor deposition is 10KPa to 0.1MPa; (6) Auxiliary carrier gas is also added during the vapor deposition process; (7) An auxiliary carrier gas is also added during the vapor deposition process, and the auxiliary carrier gas includes at least one of H2, CO2, NH3 and Ar; (8) An auxiliary carrier gas is also added during the vapor deposition process, and the flow rate of the auxiliary carrier gas is 100 mL / min to 8000 mL / min; (9) An auxiliary carrier gas is also added during the vapor deposition process, and the flow ratio of the vapor phase carbon source to the auxiliary carrier gas is (3-9.5): (0.5-7); (10) The vapor deposition is carried out in a deposition chamber of a vapor deposition device, and the rotation speed of the deposition chamber is 0.1 r / min to 10 r / min; (11) The solid phase coating agent includes tetracarboxylic anhydride, copper phthalocyanine, substituted or unsubstituted naphthalene, substituted or unsubstituted anthracene, substituted or unsubstituted phenanthrene, substituted or unsubstituted pyrene, substituted or unsubstituted biphenyl, substituted or unsubstituted terphenyl, C 60 and at least one of substituted or unsubstituted phenalene; (12) The liquid coating agent includes at least one of toluene, xylene, styrene or butyltoluene; (13) The method further comprises: classifying and drying the vapor deposited product: (14) The method further comprises: classifying and drying the vapor deposited product, wherein the drying temperature is 50°C to 120°C and the drying time is 6 hours to 48 hours.
8. The preparation method according to claim 4, characterized in that: The method further comprises: solid-phase mixing or liquid-phase mixing the vapor-deposited product with a coating material, wherein the coating material comprises at least one of nitride, metal oxide, phosphate and silicate.
9. The preparation method according to claim 8, characterized in that: The method comprises at least one of the following features (1) to (11): (1) The step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture containing the vapor-deposited product and the coating material; (2) The step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture of the vapor-deposited product and the coating material, wherein the grinding time is 0.5 h to 48.0 h; (3) The step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture containing the vapor-deposited product and the coating material, wherein the heat treatment temperature is 400° C. to 1000° C. and the heat treatment time is 1.0 h to 24.0 h; (5) The step of solid-phase mixing the vapor-deposited product with the coating material comprises: grinding and heat-treating the mixture comprising the vapor-deposited product and the coating material, wherein the heat treatment is performed under a protective atmosphere, wherein the protective atmosphere comprises at least one of nitrogen, helium, argon, neon, and krypton; (6) The step of mixing the vapor-deposited product with the coating material in liquid phase comprises: drying and heat-treating the mixed coating liquid containing the vapor-deposited product and the coating material; (7) The step of mixing the vapor-deposited product with the coating material in liquid phase comprises: drying and heat-treating a mixed coating liquid containing the vapor-deposited product and the coating material; wherein the mixed coating liquid comprises a polar solvent; (8) The step of mixing the vapor-deposited product with the coating material in liquid phase comprises: drying and heat-treating a mixed coating liquid containing the vapor-deposited product and the coating material; wherein the polar solvent comprises at least one of water, anhydrous ethanol, methanol and isopropanol; (9) The step of mixing the vapor-deposited product with the coating material in liquid phase comprises: drying and heat-treating the mixed coating liquid containing the vapor-deposited product and the coating material, wherein the drying temperature is 50° C. to 120° C. and the drying time is 6 h to 48 h; (10) The step of mixing the vapor-deposited product with the coating material in liquid phase comprises: drying and heat-treating the mixed coating liquid containing the vapor-deposited product and the coating material, wherein the heat treatment temperature is 80° C. to 150° C. and the heat treatment time is 3.0 h to 48.0 h; (11) The step of mixing the vapor-deposited product with the coating material in liquid phase includes: drying and heat treating the mixed coating liquid containing the vapor-deposited product and the coating material, wherein the heat treatment is carried out under a protective atmosphere, and the protective atmosphere includes at least one of nitrogen, helium, argon, neon, and krypton.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode material according to any one of claims 1 to 3 or the negative electrode material prepared by the method for preparing the negative electrode material according to any one of claims 4 to 9.
Citation Information
Cited By
Negative electrode material, preparation method therefor, and lithium-ion battery
EP4604205A1
Negative electrode material, preparation method therefor, and lithium-ion battery
WO2025066142A1